2012
DOI: 10.1051/medsci/2012286017
|View full text |Cite
|
Sign up to set email alerts
|

Rhumatisme articulaire aigu

Abstract: > Le rhumatisme articulaire aigu représente un modèle d'auto-immunité acquise liée à la pré-sence d'anticorps dirigés contre l'endocarde valvulaire cardiaque et qui se développent au décours d'une infection pharyngée à streptocoque. Les lésions peuvent évoluer à bas bruit vers des séquelles valvulaires (cardiopathie rhumatismale), parfois sévères et compliquées d'insuffisance cardiaque. Cette pathologie a été éradiquée des pays industrialisés grâce à l'amé-lioration du niveau de vie et aux programmes de préven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…Peña found a family history of AAR in only one patient [3]. Other authors among others [17]- [22] have found that some patients have an insidious and progressive onset of the disease. On the neuromuscular level, the upper limbs and the face were solicited by involuntary movements, hypotonia.…”
Section: Discussionmentioning
confidence: 91%
“…Peña found a family history of AAR in only one patient [3]. Other authors among others [17]- [22] have found that some patients have an insidious and progressive onset of the disease. On the neuromuscular level, the upper limbs and the face were solicited by involuntary movements, hypotonia.…”
Section: Discussionmentioning
confidence: 91%
“…These results may have been obtained because surgery eliminates diseased valvular cells and simultaneously the source of the pathology. The proteins of valvular cells similar to those of Streptococcus pyogenes [43] are the targets of immune cells. Eradication of the source of the pathology would lead to a correction between the mechanism underlying autoimmunity, and the cells involved in the defense against Streptococcus of Group A and autoimmunity would become functional again in the next generation.…”
Section: Discussionmentioning
confidence: 99%
“…Des facteurs environnementaux ou immunologiques peuvent être impliqués dans le déclenchement de ces pathologies. Par exemple, une réactivité croisée entre certains autoantigènes et des antigènes microbiens serait un des méca-nismes expliquant l'apparition d'une auto-immunité (➜) [32]. La mutation de certaines molécules régulant négativement l'activité des LT, telles que le CTLA-4 (cytotoxic T-lymphocyte antigen 4) Utilisation des nTreg CD4 + L'objectif des stratégies utilisant les nTreg est d'augmenter la quantité de nTreg fonctionnels polyclonaux chez le patient.…”
Section: Maladies Auto-immunes Et Lymphocytes T Régulateurs (Treg)unclassified